PEMBERDAYAAN PETANI JAMUR TIRAM MELALUI PELATIHAN DAN PENDAMPINGAN STRATEGI PEMASARAN PADA MASA PANDEMI COVID-19 - Sukanteri, Ni Putu; Lestari, Putu Fajar kartika; Susanti, Ida Ayu Dwi (Jurnal Abdi Insani, 2022)
Farmers in the village yet are one of the producers of oyster mushrooms in Bali. The production of oyster mushrooms is carried out to open up business opportunities for those who currently do not have a job due to the impact of the covid 19 pandemic. The purpose of this service activity is to provide training and marketing assistance for oyster mushrooms both conventionally and online. The method of activities carried out by training and mentoring mushroom farmers is carried out in several stages, namely: The stage of service activities carried out to assist partners in solving problems are (1) Preparation of service activities; (2) Counseling and assistance with an emphasis on reducing the impact of Covid-19. The implementation of the activity begins with the preparation of materials and tools, then provides counseling/training on marketing strategies and packaging of oyster mushrooms. The results of the pre test show that 53.33% of the activity partners have known about online marketing but have not done marketing in that way. Marketing training includes packaging and trademarking of oyster mushroom packaging marketed by members. So that the training activities carried out to members of the farmer group there are changes in the skills possessed by the members of the farmer group later on in daily production and marketing activities. Activities carried out in the form of counseling and training. Counseling to members of the mushroom farmer group showed an increase in knowledge of 40% from before the training. Mastery of packaging skills shows that 100% of mushroom farmer members have skills in packaging mushroom products to be marketed. Mushroom marketing has not been optimal due to constraints in production and marketing that have not been resolved.